IDENTIFIKASI TEKNIK SAMBUNGAN KAYU PADA ARSITEKTUR VERNAKULAR LAMBAN PESAGI DI LAMPUNG - Suci Lestari; Putri, Tiya Suryadi; Faris, Moh. Faisal; Dewi, Ayu Komalasari (Jurnal Qua Teknika, 2025)
Vernacular architecture represents the physical embodiment of local wisdom shaped by adaptation to environmental conditions, cultural practices, and available materials. One example of such architecture in Indonesia is Lamban Pesagi, the traditional house of the Lampung Pepadun ethnic group, which holds significant historical, cultural, and technical value. This study aims to identify and analyze the wooden joinery systems employed in the construction of Lamban Pesagi as part of efforts to preserve traditional building techniques increasingly threatened by modernization. The research adopts a qualitative, descriptive-analytical approach through field observation, visual documentation, technical sketching, and literature review. The object of study is a Lamban Pesagi structure relocated to the Lampung Museum. The findings reveal a variety of joinery techniques, including mortise-and-tenon joints, wooden pegs, ornamental clamped joints, oblique mortise-and-tenon, and lashed joints. Each joint type serves specific structural functions according to its location in the foundation, mid-structure, or roof zone and demonstrates a high level of technical sophistication. These techniques not only ensure structural strength and stability but also provide lateral flexibility and efficient use of local materials. The identified joinery systems exhibit strong potential for integration into contemporary timber construction practices focused on sustainability. The documentation and analysis of these traditional joints contribute significantly to the preservation of Nusantara’s architectural heritage and the development of sustainable construction practices rooted in indigenous knowledge.